The Contemporary Dimension of Globalization and Local Security – Conclusions from the Research - Piotr MAŚLOCH (Communications of International Proceedings, 2020)
The article deals with the problems of the contemporary, new globalization of the 21st century and presents the results of own research on the sense of security in the local dimension. The active participation of local communities in these processes are an important element in ensuring the internal security of the state in the conditions of globalization. In this approach, localism (regionalism) is a tendency consisting in the striving of local (regional) communities to achieve a high degree of self-determination. Localism and regionalism are now becoming global phenomena, which means they are not the opposite of globalization. On the contrary – these processes are treated as a supplement and/or modification of the internationalization of the economy.
Keywords: Globalization; Economy; Security; Local Security; COVID 19